2014
DOI: 10.1007/s00265-014-1828-2
|View full text |Cite
|
Sign up to set email alerts
|

Investment in a sexual signal results in reduced survival under extreme conditions in the male great tit (Parus major)

Abstract: Here, we tested for an ecologically valid cost to secondary sexual trait expression in the male great tit (Parus major). We compared the breast stripe area of a sample of males who survived extremely low night time temperatures with a sample who did not survive. Breast stripe area was significantly smaller in surviving males, suggesting a real cost of signalling in terms of survival. The relationship between breast stripe area and survival was moderated by the effects of body condition: Males with larger breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 54 publications
0
4
2
1
Order By: Relevance
“…The positive relationship between bib size and H/L ratio is inconsistent with most of the earlier studies (e.g. Minias et al 2014Minias et al , 2019Moore et al 2015;Svobodová et al 2018; but see e.g. Svobodová et al 2013).…”
Section: Discussioncontrasting
confidence: 70%
“…The positive relationship between bib size and H/L ratio is inconsistent with most of the earlier studies (e.g. Minias et al 2014Minias et al , 2019Moore et al 2015;Svobodová et al 2018; but see e.g. Svobodová et al 2013).…”
Section: Discussioncontrasting
confidence: 70%
“…The stress-linked ICHH has been supported through numerous recent studies. Moore et al (2015) found support for this hypothesis in perceived attractiveness of human male faces, and Owen-Ashley et al (2004) found that testosterone implants significantly increased plasma corticosterone in song sparrows (Melospiza melodia) and suggested that the actions of testosterone were indirect through elevated corticosterone levels suppressing the immune system. Leary and Knapp (2014) found that, while moderate increases of glucocorticoids were related to elaborate male traits and increased reproductive investment, high glucocorticoid levels negatively affected reproduction and could have androgen-suppressive effects.…”
Section: Discussionmentioning
confidence: 94%
“…Studies on short‐lived species have shown that the extent of expression of potentially costly color traits is associated with increased survival (Jennions et al , Griffith et al , Galván and Møller , Galván et al , Hõrak and Männiste ). However, at least two studies have also detected viability selection against conspicuous coloration (Keyser and Siefferman , Moore et al ) and some studies found stabilizing selection on conspicuousness (Gregoire et al , Figuerola and Senar , but see also Acker et al for disruptive viability selection on a plumage trait), suggesting that the sign and magnitude of selection exerted on coloration might be species‐ or trait‐specific (Meunier et al ). It is also suggested that at least in case of heritable melanin‐based colouration, selection may not always be directional, but may be conditional to environmental conditions (Senar et al , Roulin ).…”
mentioning
confidence: 99%